+0  
 
0
181
1
avatar

Let \(\triangle ABC\) be a right triangle, and let \(H\) be the point on side \(\overline{AB}\) so that \(\overline{CH} \perp \overline{AB}.\)

 

Here's the image (it's super dark) -----> https://latex.artofproblemsolving.com/4/8/7/4874e2ec3c94887e4c1a2173960d46a4d30c14f4.png 

 


Prove that    \((x + h)^2 + (y + h)^2 = (a + b)^2.\)

 

Thank you!
 

 Jan 24, 2020
 #1
avatar+21951 
+1

Find the area of the triangle in two different ways:

 

First way:  Area  =  ½·base·height     --->     Area  =  ½·(x + y)·h

 

Second way:  Area  =  ½·a·b·cos(C)     --->     Area  =  ½·a·b                  [cos(90°) = 1]

 

Therefore:                                                      ½·(x + y)·h  =  ½·a·b 

Multiply both sides by 4:                                 2·(x + y)·h  = 2·a·b 

Add (x2 + y2) to both sides:           (x2 + y2​) + 2·(x + y)·h  =  (x2 + y2​) + 2·a·b 

Simplify:                                          (x2 + y2​) + 2xh + 2yh  =  (x2 + y2​) + 2·a·b 

Rewrite:                                        (x2 + 2xh) + (y2 + 2yh)  =  (x2 + y2​) + 2·a·b 

Add 2h2 to both sides:   (x2 + 2xh + h2) + (y2 + 2yh + h2)  =  (x2 + y2​) + 2·a·b  + 2h2 

Factor:                                                  (x + h)2 + (y + h)2  =  (x2 + y2​) + 2·a·b  + 2h2 

Complete the square:                           (x + h)2 + (y + h)2  =  (x2 + 2xy + y2​) + 2·a·b  + 2h2 - 2xy

Rewrite:                                                (x + h)2 + (y + h)2  =  (x + y​)2 + 2·a·b  + 2h2 - 2xy

Since (x + y​)2 = c2 = a2 + b2                (x + h)2 + (y + h)2  =  (a2 + b2) + 2·a·b  + 2h2 - 2xy

Rewrite:                                               (x + h)2 + (y + h)2  =  (a2 + 2ab + b2) + 2h2 - 2xy

Rewrite:                                               (x + h)2 + (y + h)2  =  (a + b) 2+ 2h2 - 2xy

 

Going back to the triangle: h is the mean proportion between x and y:  x/h = h/y  -->  xy = h2

Therefore     2xy  =  2h2  --->   2h2 - 2xy  =  0

So:                                                        (x + h)2 + (y + h)2  =  (a + b) 2+ 0

And:                                                      (x + h)2 + (y + h)2  =  (a + b) 2

 Jan 24, 2020

16 Online Users

avatar